Solitary and joint online pornography use during the first COVID-19 lockdown in Portugal: Intrapersonal and interpersonal correlates - Rodrigues, D. L. (Cyberpsychology: Journal of Psychosocial Research on Cyberspace, 2021)
The onset of the COVID-19 pandemic forced several people into social isolation and research has shown a paradoxical effect on people’s sexual functioning. Some people experienced decreases in sexual desire and sexual satisfaction, whereas others experienced heightened sexual desire and made new additions to their sexual repertoire, including more online pornography use during the lockdown. Yet, studies failed to examine its interpersonal and intrapersonal correlates, distinguish between solitary and joint use, or explore differences between partnered and single people. We examined if changes in solitary or joint online pornography use since the lockdown were associated with sexual functioning, sexual satisfaction, perceived health, and sleep quality. We conducted an online cross-sectional study with convenience sampling in Portugal (N = 303 participants; 56.3% men; Mage = 31.32, SD = 10.55; 70.8% in a relationship) during May and July 2020. Partnered participants who reported increases in solitary online pornography use also reported decreases in their sex life quality. For partnered and single participants, increases in joint online pornography use were associated with increases in sex life quality. Single participants who reported increases in solitary online pornography use also perceived better health and sleep quality, and those who reported increases in joint online pornography use also reported more intimacy with casual partner(s) and better sleep quality. These findings suggest that online pornography was sometimes used as a sexual pleasure tool to connect with a stable or casual partner(s) in a time when social interactions were restricted.